Knowledge mapping of exosomes in metabolic diseases: a bibliometric analysis (2007-2022) - Xu, Fangzhi; Xia, Chenxi; Dou, Lin; Huang, Xiuqing (Frontiers in Endocrinology, 2023)
Background Research on exosomes in metabolic diseases has been gaining attention, but a comprehensive and objective report on the current state of research is lacking. This study aimed to conduct a bibliometric analysis of publications on “exosomes in metabolic diseases” to analyze the current status and trends of research using visualization methods. Methods The web of science core collection was searched for publications on exosomes in metabolic diseases from 2007 to 2022. Three software packages, VOSviewer, CiteSpace, and R package “bibliometrix” were used for the bibliometric analysis. Results A total of 532 papers were analyzed, authored by 29,705 researchers from 46 countries/regions and 923 institutions, published in 310 academic journals. The number of publications related to exosomes in metabolic diseases is gradually increasing. China and the United States were the most productive countries, while Ciber Centro de Investigacion Biomedica en Red was the most active institution. The International Journal of Molecular Sciences published the most relevant studies, and Plos One received the most citations. Khalyfa, Abdelnaby published the most papers and Thery, C was the most cited. The ten most co-cited references were considered as the knowledge base. After analysis, the most common keywords were microRNAs, biomarkers, insulin resistance, expression, and obesity. Applying basic research related on exosomes in metabolic diseases to clinical diagnosis and treatment is a research hotspot and trend. Conclusion This study provides a comprehensive summary of research trends and developments in exosomes in metabolic diseases through bibliometrics. The information points out the research frontiers and hot directions in recent years and will provide a reference for researchers in this field.